Urban problems in the civil town of Aquincum: the so-called „northern band” - Láng, Orsolya (Dissertationes Archaeologicae, 2013)
Abstract of PhD thesis submitted in 2013 to the Archaeology Doctoral Programme, Doctoral School of History, Eötvös Loránd University, Budapest under the supervision of Dénes Gabler.